2018
DOI: 10.1002/adfm.201800409
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cellulose for Water Purification, Antimicrobial Applications, and Sensors

Abstract: As the most abundant natural polymer, cellulose presents a unique advantage for large-scale applications. To fully unlock its potential, the introduction of desired functional groups onto the cellulose backbone is required, which can be realized by either chemical bonding or physical surface interactions. This review gives an overview of the chemistry behind the state-of-the-art functionalization methods (e.g., oxidation, esterification, grafting) for cellulose in its various forms, from nanocrystals to bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(99 citation statements)
references
References 238 publications
(243 reference statements)
0
99
0
Order By: Relevance
“…Usually, they are well usable for capacitive and resistive humidity sensing with simple electronic evaluation. 43 As stated in the review, 44 several studies confirmed that the electrical properties of cellulose are sensitive to the concentration of water vapor. 40,41 Organic materials are particularly interesting in terms of their environmental compatibility as was demonstrated on a sensor based on biopolymer Keratin, which is naturally nontoxic, biocompatible, and biodegradable.…”
Section: Introductionmentioning
confidence: 81%
“…Usually, they are well usable for capacitive and resistive humidity sensing with simple electronic evaluation. 43 As stated in the review, 44 several studies confirmed that the electrical properties of cellulose are sensitive to the concentration of water vapor. 40,41 Organic materials are particularly interesting in terms of their environmental compatibility as was demonstrated on a sensor based on biopolymer Keratin, which is naturally nontoxic, biocompatible, and biodegradable.…”
Section: Introductionmentioning
confidence: 81%
“…Cellulose is the most abundant natural polymer; it is nontoxic and inexpensive. A rational functionalization of cellulose has been shown to have applications in various areas like water purification, antibacterial action, sensing, energy harvesting, and catalysis . However, there are only a handful examples of functionalized cellulose as sensors, where chemically functionalized cellulose is used for colorimetric sensing of metal ions like Ni II , Cu II , and Fe III .…”
Section: Methodsmentioning
confidence: 99%
“…To preliminarily assess the effect of the presence of BA in BC on the adsorption of metal ions, adsorption assays of BA/BC and BC without surface functionalization were performed which may increase the adsorption capacity of cellulose [19,27]. Pb(II) was chosen as a model metal ion and the adsorption of BA/BC and BC under various conditions was assessed.…”
Section: Adsorption Capacities Of Bc and Ba/bcmentioning
confidence: 99%